A homogeneous charge compression ignition engine: an introduction - Hairuddin, Abdul Aziz; Wandel, Andrew P.; Yusaf, Talal (2013)
Homogeneous charge compression ignition (HCCI) engine technology is relatively new and has not matured sufficiently to be commercialised compared with conventional engines. It can use spark ignition (SI) or compression ignition (CI) engine configurations, capitalizing on the advantages of both: high engine efficiency with low emissions levels. The HCCI engines can use a wide range of fuels with low emissions levels. Due to these advantages, the HCCI engines are suitable to be used in a hybrid engine configuration, where it can reduce the fuel consumption even further. However, the HCCI engines have some disadvantages such as knocking and low to medium operating load range, which need to be resolved before the engine can be commercialised. Therefore, a comprehensive study has to be performed to understand the behavior of HCCI engines.